Analysis of the Relationship between Women on the Board of Directors and Performance of Companies - Ohakanu, Eseohe Nkiruka (2012)
Background The composition of board of directors has become an important issue since the onset of the financial crisis which questioned the efficiency of company boards. Several countries including the United Kingdom (UK) have taken measures to increase the number of women on company boards but the number of women on boards is still very low. Studies have been conducted on board composition and company performance and results have been varied and inconsistent hence justifying the need for this study. Objective The purpose of this study was to analyse the relationship between women on the board of directors and financial measures of company performance. Research Strategy This study was a quantitative research which made use of data relating to board composition and to company performance. The variables used in this study were; the number of women on the board, return on equity (ROE), return on assets (ROA), profit margin, gross margin, current ratio and gearing ratio. Sample Selection and Analysis The study made use of a sample of 40 companies selected randomly from across four industries; retail, travel and leisure, food and beverage and household, leisure and personal goods, on the FTSE all share index and listed on the London Stock exchange. Data was compiled and analysed using SPSS software and Analysis of Variance (ANOVA) technique. The period for which financial data was collected was mainly from 2009 to 2011. Findings The results obtained from this study showed no evidence of significant relationship between women on the board of directors and financial measures of company performance. Future studies should include quantitative and qualitative measure of company performance.